(untitled) (Baltic Journal of Sport and Health Sciences, 2025)
Background: Dynamic change of the pulmonary oxygen uptake is one of the core parameters determining the bodies’ adaptability to the varying physical load. It is equally important in both everyday life and sports. Regardless of the importance, this physiological mechanism is understudied, especially in younger population. Therefore, the aim of this study was to examine oxygen uptake kinetics at the onset and offset of exercise in terms of basketball training and maturity level in adolescent boys. Methods: Our subjects were 28 basketball-trained (BT) and 22 actively untrained (UT) boys (average age: 11.83 ± 0.43 years). Subjects performed 6-minute-long constant speed walking tests on a treadmill and a static recovery afterwards with a 1-year interval between the sessions to determine oxygen uptake, heart rate, and muscle oxygenation time constants and other parameters. Maturity level was determined by the maturity offset. Results: Basketball-trained group showed faster oxygen uptake kinetics (1st session: 13.10 ± 2.68 s and 15.02 ± 2.96 s in basketballers and control-group boys, respectively; 2nd session: 12.02 ± 2.86 s and 14.07 ± 4.18 s) during both testing sessions, while heart rate kinetics were faster in basketballers only during the 1st session (28.15 ± 10.59 s compared to 37.18 ± 15.23 s). Maturity level in both groups correlated with some of the kinetics parameters during the 2nd session. Conclusion: Young basketballers possess a faster on-transient oxygen uptake kinetics compared to their untrained peers because of the improved oxygen delivery and utilisation. A possible maturational threshold regarding pulmonary oxygen uptake kinetics in adolescents should be investigated in the future. Keywords: team sports, physical fitness, time constant, aerobic kinetics